(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
The Faculty of Engineering, specifically the Department of Civil Engineering at Tadulako University, holds a fundamental responsibility for ensuring the safety and security of its entire academic community, including students, faculty, and staff. Despite this imperative, the current safety framework faces significant vulnerabilities. A prevalent lack of understanding regarding proper evacuation protocols, coupled with suboptimal exit routes and inadequate safety facilities, creates substantial risks during critical emergencies, such as fires or earthquakes. To address these pressing concerns, a dedicated community service initiative was implemented. The primary objectives of this program were fourfold: first, to enhance the academic community’s comprehension of established emergency procedures; second, to redesign and install safe, intuitive, and universally accessible evacuation routes; third, to institutionalize regular and realistic evacuation training drills; and fourth, to establish a clear protocol for the ongoing maintenance and inspection of all safety facilities and equipment. The methodology encompassed a comprehensive analysis of existing conditions, the design of new evacuation routes that adhered to national safety standards, targeted socialization campaigns to disseminate information, and hands-on simulation exercises. The outcomes of this initiative were markedly positive. Post-implementation assessments revealed a 40% improvement in overall emergency preparedness, as measured by active participation and performance in simulation drills. Furthermore, the redesigned infrastructure successfully enhanced route accessibility, ensuring safe and efficient evacuation pathways for individuals with disabilities, thereby fostering a more inclusive and secure academic environment. Keywords: Evacuation routes, fire safety, evacuation drill, accessibility Fakultas Teknik, khususnya Jurusan Teknik Sipil di Universitas Tadulako, memiliki tanggung jawab mendasar untuk menjamin keselamatan seluruh warga kampus, termasuk mahasiswa, dosen, dan tenaga kependidikan. Namun, kondisi kesiapsiagaan darurat di lingkungan fakultas menunjukkan beberapa kelemahan kritis yang dapat membahayakan jiwa. Kerentanan utama yang teridentifikasi adalah rendahnya pemahaman tentang prosedur evakuasi, desain dan penandaan jalur penyelamatan yang kurang optimal, serta keterbatasan sarana dan fasilitas keselamatan. Hal ini menimbulkan risiko serius jika terjadi keadaan darurat seperti kebakaran atau gempa bumi. Sebagai respon, dilaksanakan program pengabdian kepada masyarakat yang berfokus pada peningkatan sistem keselamatan. Program ini dirancang dengan empat tujuan spesifik. Pertama, meningkatkan pemahaman dan kesadaran komunitas akademik terhadap prosedur tanggap darurat. Kedua, merancang dan mengimplementasikan jalur evakuasi yang tidak hanya aman, tetapi juga mudah dipahami dan dapat diakses oleh semua orang, termasuk penyandang disabilitas. Ketiga, melaksanakan pelatihan dan simulasi evakuasi secara berkala dan realistis untuk membangun respons yang terlatih. Keempat, menetapkan mekanisme yang jelas untuk pemeliharaan rutin fasilitas keselamatan. Metode pelaksanaannya meliputi beberapa tahapan: analisis mendalam terhadap kondisi eksisting dan potensi risiko, perancangan teknis jalur evakuasi berdasarkan standar nasional, kegiatan sosialisasi dan edukasi kepada sivitas akademika, serta penyelenggaraan simulasi atau gladi evakuasi. Hasil evaluasi program menunjukkan capaian yang signifikan. Terjadi peningkatan kesiapsiagaan sebesar 40% yang diukur dari tingkat partisipasi dan efektivitas selama simulasi. Selain itu, perbaikan infrastruktur fisik berhasil menciptakan jalur evakuasi yang lebih jelas dan aksesibel, secara khusus mempertimbangkan kebutuhan difabel. Dengan demikian, program ini telah berkontribusi langsung dalam mewujudkan lingkungan kampus yang lebih tanggap bencana dan aman bagi seluruh penghuninya. Kata Kunci: Jalur evakuasi, keselamatan kebakaran, simulasi evakuasi, aksesibilitas